Preparation method and application of coconut shell charcoal hard carbon material
The pore structure control of coconut shell carbon is solved by inorganic sodium salt impregnation, which solves the problems of difficult pore structure control, high energy consumption and high production cost in the preparation of hard carbon materials in the prior art, and achieves the preparation of hard carbon materials with high specific capacity, excellent electrochemical performance and low cost.
Patent Information
- Application Number
- CN202411947275.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, when preparing sodium ion battery hard carbon anode material using coconut shell charcoal as raw material, there are problems such as difficulty in regulating pore structure, high energy consumption and high production costs.
The pore structure of coconut shell charcoal is controlled by inorganic sodium salt impregnation method. Through acid solution treatment and inorganic sodium salt solution impregnation, combined with high temperature tube furnace heating and ball milling treatment, hard carbon materials with high specific surface area and ideal pore size distribution are prepared.
The specific capacity improvement, magnification and cycle stability performance of hard carbon materials are achieved, reducing energy consumption and production costs, and improving the cycle life and overall performance of sodium ion batteries.
Smart Images

Figure CN119706840A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a preparation method and application of a coconut shell charcoal hard carbon material. Background Art
[0002] Lithium-ion batteries, as common rechargeable batteries, offer advantages such as high energy density, long cycle life, and high output voltage. However, due to the low content and uneven distribution of lithium in the Earth's crust, the widespread use of lithium-ion batteries has led to a sharp increase in demand for lithium resources, resulting in a tight supply of lithium resources. Sodium, a metallic element in the same main group as lithium, is extremely abundant in the Earth's crust. Furthermore, sodium-ion batteries have long cycle life, fast charge and discharge speeds, and excellent low-temperature performance. Therefore, promoting their use can effectively alleviate the shortage of lithium resources and is of great significance to the long-term development of new energy and downstream industries.
[0003] The structure of a sodium-ion battery mainly includes a positive electrode, a negative electrode, an electrolyte, a current collector, a separator, and a casing. Among them, the negative electrode material plays the role of loading and releasing sodium ions and is a key material for sodium-ion batteries. There are four main types of negative electrode materials for sodium-ion batteries: carbon-based materials, titanium-based materials, alloy-based materials, and organic compound materials. Due to the limitations of the kinetic size of sodium ions, carbon-based materials generally use hard carbon as the negative electrode, that is, hard carbon negative electrode materials. Although the capacity of hard carbon negative electrode materials is lower than that of other types of negative electrode materials, their stable structure gives sodium-ion batteries excellent long-cycle stability and low-temperature performance. More importantly, hard carbon negative electrode materials are non-toxic and low-cost. Therefore, hard carbon negative electrode materials have become the mainstream direction of negative electrode materials for sodium-ion batteries.
[0004] Currently, hard carbon anode materials for sodium-ion batteries can be categorized into three types based on their carbonaceous precursors: biomass-based, asphalt-based, and resin-based. Chinese patent application CN202410921620.2 discloses a resin-based hard carbon anode material, its preparation method, and its application. This type of resin-based hard carbon anode material, due to its organic compound precursors, is complex to manufacture and requires costly measures to meet environmental and safety assessment requirements. This results in high costs for these hard carbon anode materials.
[0005] Chinese patent CN117352652A discloses a method for preparing and applying a high-performance pitch-based hard carbon anode material for sodium-ion batteries. To improve the yield of the hard carbon anode material, the medium-temperature pitch must be oxidized to produce a high-softening-point pitch, which inevitably increases the raw material cost. Furthermore, the high sulfur and nitrogen content of high-softening-point coal tar or petroleum tar further increases the production cost of the pitch-based hard carbon anode material.
[0006] Biomass-based hard carbon anode materials offer significant advantages over resin- and pitch-based hard carbon anode materials. First, biomass is widely available and inexpensive. Second, biomass has a high carbon content and is primarily composed of fused-ring compounds. This offers a significant cost advantage while maintaining comparable electrochemical performance.
[0007] Among biomass materials, coconut shell charcoal has attracted attention due to its widespread availability, high carbon content, and low ash content. The production of hard carbon anode materials for sodium-ion batteries using coconut shell charcoal typically involves two key steps: pore formation and high-temperature carbonization. The pore formation process is crucial for influencing the electrochemical performance of hard carbon anode materials.
[0008] Physical activation methods, such as water vapor or carbon dioxide activation, and chemical activation methods, such as potassium hydroxide or sodium hydroxide activation, are commonly used pore-forming methods in academia and industry, but both have shortcomings in the application of coconut shell charcoal as raw material.
[0009] Physical activation methods suffer from the problem of gas blowing out the powdered coconut shell charcoal, making it difficult to control the pore structure of the coconut shell charcoal, such as specific surface area, pore diameter, and yield. Furthermore, the long activation time at high temperatures leads to high energy consumption. Chemical activation methods also suffer from alkaline corrosion and high wastewater treatment costs. Furthermore, both physical and chemical activation methods produce coconut shell charcoal hard carbon anode materials with a wide pore size distribution, which is not conducive to increasing the capacity of the hard carbon anode.
[0010] In summary, how to provide a method for preparing hard carbon materials suitable for coconut shell charcoal raw materials is a technical problem that urgently needs to be solved. Summary of the Invention
[0011] The purpose of the present invention is to overcome the shortcomings of the existing technology and provide a preparation method and application of coconut shell charcoal hard carbon material. By regulating the pore structure of coconut shell charcoal with inorganic sodium salt, a coconut shell hard carbon negative electrode material with high specific capacity, good rate and cycle stability is prepared.
[0012] The present invention provides a method for preparing an inorganic sodium salt-impregnated coconut shell hard carbon negative electrode material, comprising the following steps: S1 crushes coconut shell charcoal to obtain coconut shell carbon powder, and then treats it with an acidic solution to remove impurities to obtain precursor A; S2: adding precursor A to an inorganic sodium salt solution prepared from a solid inorganic sodium salt, stirring until the inorganic sodium salt is fully impregnated; filtering after impregnation, and drying the filter cake obtained after filtration in a vacuum oven to obtain precursor B; S3 places precursor B in a tube furnace and heats it under inert atmosphere to obtain precursor C; The precursor C was kept warm and then ground, and the ground precursor C was thoroughly washed with deionized water. After filtration, the filter cake was placed in a vacuum oven to dry; S4 places the dried precursor C in a high-temperature tube furnace, heats it under the protection of an inert atmosphere, and obtains a hard carbon material after cooling.
[0013] Furthermore, the particle size of the coconut shell carbon powder in S1 ranges from 5 to 20 μm.
[0014] Furthermore, S1 includes crushing the coconut shell charcoal for 5-20 minutes using a crusher with a capacity of 5-100 g and a rotation speed of 2000-5000 r / min.
[0015] Furthermore, the acidic solution in S1 is one or more of hydrochloric acid, sulfuric acid, nitric acid, and hydrofluoric acid, with a mass concentration of 5-30%.
[0016] Further, the stirring time in S2 is 6-12h; S2 includes placing the filter cake in a vacuum oven at 80° C. and drying it for at least 12 hours to obtain precursor B.
[0017] Furthermore, the inert atmosphere in S3 is one of nitrogen, argon, and neon, with a gas flow rate of 100-600 ml / min, a heating rate of 1-5°C / min, a holding time of 2-10 h, and natural cooling; S3 includes heating the precursor B to 700-900° C. to obtain the precursor C, keeping the precursor C at 700° C. for two hours, and then grinding it.
[0018] Furthermore, the inert atmosphere in S4 is one of nitrogen, argon, and neon, with a gas flow rate of 100-600 ml / min, a heating rate of 2-6°C / min, and a holding time of 0.5-5 h; S4 includes heating the precursor C to 1100-1600° C., and then adjusting the cooling rate to be the same as the absolute value of the heating rate, so that the precursor C is first cooled to 600° C., and then continues to cool to room temperature under natural conditions.
[0019] Furthermore, after obtaining the hard carbon material, the method further includes using a ball mill to ball mill the obtained hard carbon material, wherein the ball mill speed is 100-500 r / min and the ball milling time is 0.5-2 h.
[0020] The present invention provides an inorganic sodium salt-impregnated coconut shell hard carbon material prepared by any of the above methods.
[0021] The present invention provides a sodium ion battery, the negative electrode of which comprises the inorganic sodium salt-impregnated coconut shell hard carbon material as described above.
[0022] Due to the adoption of the above technical solution, the present invention has the following advantages and positive effects compared with the prior art, as an example: The inorganic sodium salt impregnation method effectively regulates the pore structure of hard carbon materials, resulting in superior electrochemical performance. This method overcomes the shortcomings of traditional physical and chemical activation methods in pore structure optimization, achieving a higher specific surface area and a more ideal pore size distribution. Furthermore, compared with traditional carbonization and activation methods, the impregnation method of the present invention significantly reduces energy consumption. By optimizing process parameters, the time and temperature of high-temperature treatment are reduced, improving the energy efficiency of the overall process.
[0023] Using the hard carbon material prepared in this invention as the negative electrode for sodium-ion batteries significantly improves the battery's capacity and cycling stability. The optimized pore structure enhances the material's electrical conductivity and ion conduction, thereby improving the battery's overall performance. During the sodium-ion battery's charge and discharge processes, it exhibits improved cycle life and reduced capacity decay.
[0024] Furthermore, the method of the present invention allows for flexible adjustment of the type and concentration of inorganic sodium salts to meet diverse hard carbon material production requirements, demonstrating strong process adaptability and scalability. The coconut shell charcoal used in the present invention is a plentiful and renewable raw material, and the entire preparation process is relatively environmentally friendly, minimizing environmental pollution and meeting the requirements of sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic diagram of the steps of the method for preparing the coconut shell charcoal hard carbon material provided by the present invention.
[0026] Figure 2 This is a thermogravimetric comparison diagram of the intermediate of Example 1 and Comparative Example 1 of the present invention. In the figure, the vertical axis is the mass percentage (%) Figure 3 This is a charge and discharge curve diagram of the hard carbon material obtained in Example 2 of the present invention.
[0027] Figure 4 This is a cycle diagram of embodiment 1 of the present invention. DETAILED DESCRIPTION
[0028] The technical solutions disclosed in the present invention are further described in detail below with reference to the accompanying drawings and specific embodiments. It should be noted that the technical features or combinations of technical features described in the following embodiments should not be considered isolated, and they can be combined with each other to achieve better technical effects.
[0029] Techniques, methods, and apparatus known to persons of ordinary skill in the relevant art may not be discussed in detail, but where appropriate, such techniques, methods, and apparatus should be considered part of the specification. In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.
[0030] The present invention provides a method for preparing an inorganic sodium salt impregnated coconut shell hard carbon negative electrode material. Figure 1 As shown, the following steps are included: S1 crushes coconut shell charcoal to obtain coconut shell carbon powder, and then treats it with an acidic solution to remove impurities to obtain precursor A; S1 includes pre-carbonization before crushing the coconut shell charcoal. As an example but not a limitation, the pre-carbonization temperature is 400-600° C. and the pre-carbonization time is 3-5 hours.
[0031] The particle size of coconut shell carbon powder in S1 ranges from 5 to 20 μm.
[0032] S1 crushes the coconut shell charcoal, including using a crusher with a capacity of 5-100 g and a rotation speed of 2000-5000 r / min to crush the coconut shell charcoal for 5-20 minutes.
[0033] The acidic solution in S1 is one or more of hydrochloric acid, sulfuric acid, nitric acid, and hydrofluoric acid, with a mass concentration of 5-30%.
[0034] S2 prepares a sodium salt solution made from solid inorganic sodium salt, adds precursor A to the sodium salt solution, wherein the mass ratio of precursor A to solid sodium salt is between 1:2 and 1:10, and stirs until the sodium salt is fully impregnated; after impregnation, filter and place the filter cake obtained after filtration in a vacuum oven to dry to obtain precursor B.
[0035] The inorganic sodium salt in S2 is one or more of sodium chloride, sodium nitrate, and sodium sulfate, and the prepared inorganic sodium salt solution has a mass concentration of 5-30%.
[0036] The stirring time is 6-12h.
[0037] For example, as an example but not a limitation, the mass ratio of precursor A to sodium chloride is 1:4, and the stirring time is 8 hours.
[0038] S2 includes placing the filter cake in a vacuum oven at 80° C. and drying it for at least 12 hours to obtain precursor B.
[0039] S3: Precursor B is placed in a tube furnace and heated under an inert atmosphere to obtain precursor C; precursor C is kept warm and then ground, the ground precursor C is thoroughly washed with deionized water, and the resulting filter cake is dried in a vacuum oven after filtration; The inert atmosphere in S3 is one of nitrogen, argon, and neon, with a gas flow rate of 100-600 ml / min, a heating rate of 1-5°C / min, a holding time of 2-10 h, and natural cooling to room temperature.
[0040] During the carbonization process, inorganic sodium salt undergoes ion exchange reaction on the surface of activated carbon, resulting in changes in the charge distribution on the surface of activated carbon.
[0041] This chemical reaction generates a highly oxidizing reactive oxygen species, which etch the activated carbon surface. On the other hand, due to the formation of primary pores, ultrafine sodium chloride can enter the activated carbon interior, further adjusting the pore structure.
[0042] S3 includes heating the precursor B to 700-900° C. to obtain the precursor C, keeping the precursor C at 700° C. for two hours, and then grinding it.
[0043] The filtration device is provided as an example and not as a limitation, and includes a circulating water vacuum pump, a 1000 mL filtration bottle, a 110 mm Buchner funnel, and an 8 mm rubber tube. The obtained precursor is filtered at least three times with deionized water.
[0044] S4 places the dried precursor C in a high-temperature tube furnace, heats it under the protection of an inert atmosphere, and obtains a hard carbon material after cooling.
[0045] The inert atmosphere in S4 is one of nitrogen, argon, and neon, with a gas flow rate of 100-600 ml / min, a heating rate of 2-6° C. / min, and a holding time of 0.5-5 h.
[0046] S4 includes heating the precursor C to 1100-1600° C., and then adjusting the cooling rate to be the same as the absolute value of the heating rate, so that the precursor C is first cooled to 600° C., and then continues to cool to room temperature under natural conditions.
[0047] During the high-temperature pyrolysis process, ultrafine sodium oxide nanoparticles and sodium element activate and catalyze graphitization of carbon intermediates, effectively regulating the micropore structure of activated carbon and improving the thermal stability of activated carbon.
[0048] Furthermore, after obtaining the hard carbon material, the method further includes using a ball mill to ball mill the obtained hard carbon material, with the ball mill speed being 100-500 r / min and the ball milling time being 0.5-2 h.
[0049] During the ball milling process, the hard carbon material particles are broken due to the action of mechanical force, so that the pore structure of the material is gradually exposed and gradually eliminated under the action of long-term ball milling. As the pore structure is eliminated, the specific surface area of the material will decrease significantly and the crystallinity will increase. Correspondingly, the compaction density of the material will increase significantly, which helps to improve the overall performance of the carbon material, especially its ability to store sodium ions. On the other hand, through ball milling, the interlayer spacing of the carbon material is increased, which is conducive to the insertion and removal of sodium ions, thereby improving the cycle performance of sodium ion batteries. The prepared high-performance coconut shell hard carbon material has high efficiency for the first time, good cycle performance, simple preparation process, and huge potential for industrial production.
[0050] The following are examples of the specific implementation process: [Example 1] S1: Weigh 10g of pre-carbonized coconut shell charcoal at room temperature and crush it in a 50g commercial crusher for 5 minutes. Weigh 3.5g of the crushed coconut shell charcoal and 35g of a 10% dilute hydrochloric acid solution in a 250mL beaker. Stir for 5 hours to remove impurities from the coconut shell charcoal. Wash the acid-washed coconut shell charcoal three times with deionized water and then dry it in a vacuum oven at 80°C until it is completely dry, obtaining Precursor A.
[0051] S2: Weigh 3g of Precursor A and 30g of 10% sodium chloride solution in a 250mL beaker. Stir and immerse for 10 hours. Dry the beaker in an 80°C vacuum oven for 12 hours until the material is fully dry, obtaining Precursor B.
[0052] In step S3, precursor B was placed in a tube furnace and heated to 700°C at a heating rate of 2°C / min in a nitrogen atmosphere to obtain precursor C. This was then kept at 700°C for two hours and then ground. The precursor was washed three times with deionized water and dried in a vacuum oven at 80°C.
[0053] In step S4, the precursor D is placed in a high-temperature tube furnace and heated to 1300°C at a heating rate of 2°C / min under a nitrogen atmosphere, and kept at this temperature for 2 hours. After cooling, a hard carbon material is obtained.
[0054] S5: ball milling the obtained hard carbon material at a rotation speed of 300 r / min for 2 h to obtain a hard carbon negative electrode material for sodium ion battery.
[0055] The hard carbon negative electrode material for sodium ion batteries prepared in this embodiment was assembled into CR2032 button batteries and subjected to electrochemical performance testing. The specific capacity of the hard carbon negative electrode material reached 302.4 mAh / g, the initial efficiency was 88.7%, and the capacity retention rate after 1000 cycles was 96.8%.
[0056] [Example 2] S1: Weigh 10g of pre-carbonized coconut shell charcoal at room temperature and crush it in a 50g commercial crusher for 5 minutes. Weigh 3.5g of the crushed coconut shell charcoal and 35g of a 10% dilute hydrochloric acid solution in a 250mL beaker. Stir for 5 hours to remove impurities from the coconut shell charcoal. Wash the acid-washed coconut shell charcoal three times with deionized water and then dry it in a vacuum oven at 80°C until completely dry, obtaining Precursor A.
[0057] S2: Weigh 3g of Precursor A and 30g of 10% sodium chloride solution in a 250mL beaker. Stir and immerse for 10 hours. Dry the beaker in an 80°C vacuum oven for 12 hours until the material is fully dry, obtaining Precursor B.
[0058] In step S3, precursor B was placed in a tube furnace and heated to 700°C at a heating rate of 2°C / min in a nitrogen atmosphere to obtain precursor C. This was then kept at 700°C for two hours and then ground. The precursor was washed three times with deionized water and dried in a vacuum oven at 80°C.
[0059] S4: Place the dried precursor C in a high-temperature tube furnace, heat it to 1500°C at a heating rate of 2°C / min in a nitrogen atmosphere, keep it warm for 2 hours, and obtain a hard carbon material after cooling.
[0060] S5: ball milling the obtained hard carbon material at a rotation speed of 300 r / min for 2 h to obtain a hard carbon negative electrode material for sodium ion battery.
[0061] The hard carbon negative electrode material for sodium ion batteries prepared in this embodiment was assembled into CR2032 button batteries and subjected to electrochemical performance testing. The specific capacity of the hard carbon negative electrode material reached 316.4 / g, the initial efficiency was 90.1%, and the capacity retention rate after 1000 cycles was 97.2%.
[0062] The experimental results of Examples 1 and 2 are shown in the attached diagrams. Figure 2-4 .
[0063] [Example 3] S1: Weigh 10g of pre-carbonized coconut shell charcoal at room temperature and crush it in a 50g commercial crusher for 5 minutes. Weigh 3.5g of the crushed coconut shell charcoal and 35g of a 10% dilute hydrochloric acid solution. Place the coconut shell charcoal and the dilute hydrochloric acid solution in a 250mL beaker and stir for 5 hours to fully remove impurities. Wash the acid-washed coconut shell charcoal three times with deionized water and then dry it in a vacuum oven at 80°C until it is completely dry, obtaining Precursor A.
[0064] S2: Weigh 3g of Precursor A and 90g of 10% sodium chloride solution into a 250mL beaker and immerse for 10 hours with stirring. Dry the immersion beaker in an 80°C vacuum oven for 12 hours until the material is fully dry to obtain Precursor B.
[0065] S3 placed precursor B into a tube furnace and heated it to 700°C at a heating rate of 2°C / min in a nitrogen atmosphere to obtain precursor C. After keeping it at 700°C for two hours, it was ground, washed repeatedly with deionized water three times, and then placed in a vacuum oven at 80°C for drying.
[0066] S4: Place the dried precursor C in a high-temperature tube furnace, heat it to 1500°C at a heating rate of 2°C / min in a nitrogen atmosphere, keep it warm for 2 hours, and obtain a hard carbon material after cooling.
[0067] S5: ball milling the obtained hard carbon material at a rotation speed of 300 r / min for 2 h to obtain a hard carbon negative electrode material for sodium ion battery.
[0068] The hard carbon negative electrode material for sodium ion batteries prepared in this embodiment was assembled into CR2032 button batteries and subjected to electrochemical performance testing. The specific capacity of the hard carbon negative electrode material reached 298.8 mAh / g, the initial efficiency was 87.2%, and the capacity retention rate after 1000 cycles was 94.3%.
[0069] [Example 4] S1: Weigh 10g of pre-carbonized coconut shell charcoal at room temperature and crush it in a 50g commercial crusher for 5 minutes. Weigh 3.5g of the crushed coconut shell charcoal and 35g of a 10% dilute nitric acid solution in a 250mL beaker. Stir for 5 hours to remove impurities from the coconut shell charcoal. Wash the acid-washed coconut shell charcoal three times with deionized water and then dry it in a vacuum oven at 80°C until it is completely dry, obtaining Precursor A.
[0070] S2: Weigh 3g of Precursor A and 90g of a 10% sodium chloride solution in a 250mL beaker. Stir and immerse for 10 hours. Dry the beaker in an 80°C vacuum oven for 12 hours until the material is fully dry, obtaining Precursor B.
[0071] S3 placed precursor B into a tube furnace and heated it to 700°C at a heating rate of 2°C / min in a nitrogen atmosphere to obtain precursor C. After keeping it at 700°C for two hours, it was ground, washed repeatedly with deionized water three times, and then placed in a vacuum oven at 80°C for drying.
[0072] In step S4, the dried precursor C is placed in a high-temperature tube furnace and heated to 1500° C. at a heating rate of 2° C. / min under a nitrogen atmosphere, and kept at this temperature for 2 hours. After cooling, a hard carbon material is obtained.
[0073] S5: ball milling the obtained hard carbon material at a rotation speed of 300 r / min for 2 h to obtain a hard carbon negative electrode material for sodium ion battery.
[0074] The hard carbon negative electrode material for sodium ion batteries prepared in this embodiment was assembled into CR2032 button batteries and subjected to electrochemical performance testing. The specific capacity of the hard carbon negative electrode material reached 295.4 mAh / g, the initial efficiency was 89.2%, and the capacity retention rate after 1000 cycles was 92.3%.
[0075] [Example 5] S1: Weigh 10g of pre-carbonized coconut shell charcoal at room temperature and crush it in a 50g commercial crusher for 5 minutes. Weigh 3.5g of the crushed coconut shell charcoal and 35g of a 10% dilute hydrochloric acid solution in a 250mL beaker. Stir for 5 hours to remove impurities from the coconut shell charcoal. Wash the acid-washed coconut shell charcoal three times with deionized water and then dry it in a vacuum oven at 80°C until completely dry, obtaining Precursor A.
[0076] S2: Weigh 3g of Precursor A and 30g of 10% sodium chloride solution in a 250mL beaker. Stir and immerse for 10 hours. Dry the beaker in an 80°C vacuum oven for 12 hours until the material is fully dry, obtaining Precursor B.
[0077] S3 placed the precursor B into a tube furnace and heated it to 700°C at a heating rate of 2°C / min in a nitrogen atmosphere to obtain the precursor C. After being kept at 700°C for two hours, the precursor C was ground, washed three times with deionized water, and dried in a vacuum oven at 80°C.
[0078] In step S4, the dried precursor C is placed in a high-temperature tube furnace and heated to 1300° C. at a heating rate of 2° C. / min under a nitrogen atmosphere, and kept at this temperature for 2 hours. After cooling, a hard carbon material is obtained.
[0079] S5: ball milling the obtained hard carbon material at a rotation speed of 300 r / min for 2 h to obtain a hard carbon negative electrode material for sodium ion battery.
[0080] The hard carbon negative electrode material for sodium ion batteries prepared in this embodiment was assembled into CR2032 button batteries and subjected to electrochemical performance testing. The specific capacity of the hard carbon negative electrode material reached 308.9 mAh / g, the initial efficiency was 83.8%, and the capacity retention rate after 1000 cycles was 93.8%.
[0081] [Comparative Example 1] At room temperature, 10g of pre-carbonized coconut shell charcoal was crushed in a 50g commercial crusher for 5 minutes. 3.5g of the crushed coconut shell charcoal was weighed and placed in a 250mL beaker with 35g of a 10% dilute hydrochloric acid solution. The mixture was stirred for 5 hours to remove impurities from the coconut shell charcoal. The acid-washed coconut shell charcoal was washed three times with deionized water and then dried in a vacuum oven at 80°C until completely dry, yielding Precursor A.
[0082] Precursor A was placed in a tube furnace, heated to 700°C at a heating rate of 2°C / min in a nitrogen atmosphere, and kept at 700°C for two hours before being ground to obtain precursor B.
[0083] Precursor B was placed in a high-temperature tube furnace and heated to 1300°C at a rate of 2°C / min under a nitrogen atmosphere. The temperature was then maintained for 2 hours. After cooling, a hard carbon material was obtained. The resulting hard carbon material was ball-milled at 300 rpm for 2 hours to obtain a hard carbon anode material for sodium-ion batteries.
[0084] The sodium ion battery prepared in this comparative example was assembled into a CR2032 button battery with a hard carbon negative electrode material and subjected to electrochemical performance testing. The specific capacity of the hard carbon negative electrode material dropped to 276.5 mAh / g, the initial efficiency dropped to 72.1%, and the capacity retention rate after 1000 cycles was 85.2%.
[0085] [Comparative Example 2] At room temperature, weigh 10g of pre-carbonized coconut shell charcoal and crush it in a 50g commercial crusher for 5 minutes. Weigh 3g of precursor A and 30g of 10% sodium chloride solution, place precursor A and sodium chloride solution together in a 250mL beaker, and stir and impregnate for 10 hours. Place the impregnated beaker in an 80℃ vacuum oven and dry it for 12 hours until the material is fully dry to obtain precursor B. Place precursor B in a tube furnace and heat it to 700℃ at a heating rate of 2℃ / min in a nitrogen atmosphere. After keeping it at 700℃ for two hours, grind it, wash it repeatedly with deionized water three times, and dry it in an 80℃ vacuum oven to obtain precursor C. Place precursor C in a high-temperature tube furnace and heat it to 1300℃ at a heating rate of 2℃ / min in a nitrogen atmosphere and keep it at this temperature for 2 hours. After cooling, a hard carbon material is obtained. The obtained hard carbon material was ball-milled at a rotation speed of 300 r / min for 2 h to obtain a hard carbon negative electrode material for sodium ion batteries.
[0086] The sodium ion battery prepared in this comparative example was assembled into a CR2032 button cell with a hard carbon negative electrode material and subjected to electrochemical performance testing. The specific capacity of the hard carbon negative electrode material reached 262.6 mAh / g, the initial efficiency was 72.3%, and the capacity retention rate after 1000 cycles was 88.7%. Within the scope of protection intended by the present disclosure, terms such as "including" and "comprising" should be interpreted as inclusive or open-ended rather than exclusive or closed by default, unless expressly defined to the contrary. All technical, scientific, or other terms have the meanings understood by those skilled in the art unless expressly defined to the contrary. Common terms found in dictionaries should not be interpreted in an overly idealistic or unrealistic manner in the context of relevant technical documents, unless expressly defined to that extent by the present disclosure.
[0087] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims, not the foregoing description, and all variations within the meaning and range of equivalents of the claims are intended to be included therein. Any reference sign in a claim should not be construed as limiting the claim to which it relates.
[0088] In addition, it should be understood that although this specification is described in terms of implementation methods, not every implementation method contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.
Claims
1. A method for preparing an inorganic sodium salt impregnated coconut shell hard carbon negative electrode material, characterized in that: The steps include: S1 crushes coconut shell charcoal to obtain coconut shell carbon powder, and then treats it with an acid solution to remove impurities to obtain precursor A; S2 prepares an inorganic sodium salt solution prepared from a solid inorganic sodium salt, adds the precursor A to the inorganic sodium salt solution, and stirs until the inorganic sodium salt is fully impregnated; After the impregnation is completed, the filter cake is filtered and placed in a vacuum oven to dry to obtain precursor B; S3 places the precursor B in a tube furnace and heats it under the protection of an inert atmosphere to obtain the precursor C; The precursor C is kept warm and then ground, the ground precursor C is fully washed with deionized water, and the obtained filter cake is placed in a vacuum oven for drying after suction filtration; S4 places the dried precursor C in a high-temperature tube furnace, heats it under the protection of an inert atmosphere, and obtains a hard carbon material after cooling.
2. The method for preparing the inorganic sodium salt impregnated coconut shell hard carbon negative electrode material according to claim 1, characterized in that: S1 also includes pre-carbonization before crushing the coconut shell charcoal, the pre-carbonization temperature is 400-600℃, and the pre-carbonization time is 3-5h; S1 crushes the coconut shell charcoal, including using a crusher with a capacity of 5-100g and a rotation speed of 2000-5000r / min to crush the coconut shell charcoal for 5-20min.
3. The method for preparing the inorganic sodium salt impregnated coconut shell hard carbon negative electrode material according to claim 1, characterized in that: The acidic solution in S1 is one or more of hydrochloric acid, sulfuric acid, nitric acid, and hydrofluoric acid, with a mass concentration of 5-30%; The particle size of coconut shell carbon powder in S1 ranges from 5 to 20 μm.
4. The method according to claim 1, characterized in that: In S2, the inorganic sodium salt is one or more of sodium chloride, sodium nitrate, and sodium sulfate, and the mass concentration of the prepared inorganic sodium salt solution is 5-30%.
5. The method according to claim 4, characterized in that: In S2, the mass ratio of the precursor A to the solid sodium salt is between 1:2 and 1:10; S2 includes adding precursor A to an inorganic sodium salt solution and stirring for 6-12 hours; S2 includes placing the filter cake in a vacuum oven at 80° C. and drying it for at least 12 hours to obtain precursor B.
6. The method according to claim 1, characterized in that: The inert atmosphere in S3 is one of nitrogen, argon and neon, the gas flow rate is 100-600 ml / min, the heating rate is 1-5 ° C / min, the insulation time is 2-10h, and natural cooling is performed; S3 includes heating the precursor B to 700-900° C. to obtain the precursor C, and grinding the precursor C after keeping it at 700° C. for two hours.
7. The method according to claim 1, characterized in that: The inert atmosphere in S4 is one of nitrogen, argon and neon, the gas flow rate is 100-600 ml / min, the heating rate is 2-6°C / min, and the holding time is 0.5-5h; S4 includes heating the precursor C to 1100-1600° C., and then adjusting the cooling rate to be the same as the absolute value of the heating rate, so that the precursor C is first cooled to 600° C., and then continues to cool to room temperature under natural conditions.
8. The method according to claims 1-7, characterized in that: After obtaining the hard carbon material, the method further includes using a ball mill to ball mill the obtained hard carbon material, wherein the speed of the ball mill is 100-500 r / min and the ball milling time is 0.5-2h.
9. An inorganic sodium salt-impregnated coconut shell hard carbon material prepared by the method as claimed in any one of claims 1 to 8.
10. A sodium ion battery, characterized in that: The negative electrode comprises a coconut shell hard carbon material impregnated with an inorganic sodium salt as described in claim 9.
Citation Information
Patent Citations
Preparation method and application of high-performance sodium ion battery hard carbon negative electrode material
CN117352652A
Resin-based hard carbon negative electrode material, preparation method thereof and sodium ion battery
CN118754095A
Cited By
Preparation method of activated carbon for improving COD (Chemical Oxygen Demand) removal efficiency
CN120398050A